1966
DOI: 10.2307/2694457
|View full text |Cite
|
Sign up to set email alerts
|

Archaeological and Paleoethnobotanical Investigations in Salts Cave, Mammoth Cave National Park, Kentucky

Abstract: Reconnaissance, surface collecting, and test excavation were carried on in Salts Cave in August, 1963, by a joint Illinois State Museum-Cave Research Foundation expedition in cooperation with the National Park Service. Various analyses and secondary investigations have continued since then. The main upper passages of the cave were extensively visited during the last millennium B.C. by a prehistoric people who are probably to be assigned to the Early Woodland culture grouping. They were exploiting the mineral r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

1972
1972
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 4 publications
0
16
0
1
Order By: Relevance
“…The history of coprolite analysis as an archaeological 'discipline' in the Americas has been traced back to the 1950s and 60s with a heavy focus on diet through plant macrobotanical remains (Callen and Cameron 1955, Callen and Martin 1968, Watson and Yarnell 1966, though Jones emphasized the need for comparative studies with botanical and faunal material as early as 1936. Callen (1967) for example analysed plant and animal macro and microfossils from 116 human coprolites representing seven phases of human occupation at Tehuacan, Mexico.…”
Section: The History Of Coprolite Analysis In Archaeologymentioning
confidence: 99%
“…The history of coprolite analysis as an archaeological 'discipline' in the Americas has been traced back to the 1950s and 60s with a heavy focus on diet through plant macrobotanical remains (Callen and Cameron 1955, Callen and Martin 1968, Watson and Yarnell 1966, though Jones emphasized the need for comparative studies with botanical and faunal material as early as 1936. Callen (1967) for example analysed plant and animal macro and microfossils from 116 human coprolites representing seven phases of human occupation at Tehuacan, Mexico.…”
Section: The History Of Coprolite Analysis In Archaeologymentioning
confidence: 99%
“…Following the development of this rehydration technique, Callen and others began a systematic study of the pollen, plant and animal macrofossils, and parasitological remains recovered from these unique human (Bryant 1969(Bryant , 1974b(Bryant , c, 1975Callen 1963;Callen and Martin 1969;Colyer 1965;Dickson et al 2003;Fry 1970;Fry and Moore 1969;Heizer 1967;Martin and Sharrock 1964;Moore 1969;Riskind 1970;Robbins 1971;Watson and Yarnell 1966;Yarnell 1969). While the recovery of macrofossils, pollen, and parasitological data has been the main focus of coprolite studies, recent research has also extended into areas of biochemical analysis including…”
Section: A Brief History Of Coprolite Researchmentioning
confidence: 99%
“…It has been amply demonstrated that sumpweed achenes were eaten during the first millennium B.C. (Jones 1936:151;Watson and Yarnell 1966;Yarnell 1969a). Proto-historic use may have paralleled sunflower seed utilization as a source of oil.…”
Section: Archaeological Recoveriesmentioning
confidence: 99%